PC.05 Improving standards of care in early onset neonatal sepsis. (9th June 2014) - Woodgate, L; Verow, R; Nicholl, R
Abstract : Aim: Guidance on preventing and managing early-onset neonatal sepsis was outdated and confusing, leading to: variation in practice, inappropriate antibiotic use, prolonged inpatient stay, suboptimal management of suspected sepsis. Method: Management of early-onset neonatal sepsis practice was audited against NICE guidance 1 in September 2012 for all neonates on the postnatal ward. The primary standard was indication for commencing antibiotics as per criteria from NICE, with secondary standards of initial and 36hr C-reactive protein (CRP), blood culture (BC), lumbar puncture (LP), antibiotic duration, daily paediatric review, documented discharge advice to parents and completed GP discharge summary. Results were reviewed alongside NICE guidance and multidisciplinary team consultation before formulating new guidance. Following implementation of changes, practice was re-audited in May 2013. Results: 46 neonates (10.1% of births) were commenced on antibiotics pre-guideline introduction compared to 28 neonates (6.9%) post-guideline (p = 0.11). The proportion meeting criteria for commencing antibiotics was significantly improved post-guideline introduction (100% vs 61%, .01). Secondary standards showed a trend of improvement; documented advice to parents significantly improved (32% vs 6.8%, p = 0.01). Conclusions: Unified guidelines promote confidence in managing early-onset sepsis, improving patient safety and engaging adherence to guidelines to facilitate change. Workload for neonatal nursing staff is reduced and guidance allows easier decision-making for junior medical staff. Overall, reviewing the need for antibiotics in the management of suspected and confirmed neonatal sepsis decreases inappropriate antibiotic usage. To maintain and improve standards, a septic care-bundle is being introduced to link in with the new transitional care unit. Reference: National Institute for Health and Care Excellence. Antibiotics for early-onset neonatal infection. CG149. London: National Institute for Health and Care Excellence. for Health and Care Excellence. 2012